Possible relationship between the Earth's rotation variations and geomagnetic field reversals over the past 510 Myr - Pacca, Igor G.; Frigo, Everton; Hartmann, Gelvam A. (Frontiers in Earth Science, 2015)
The Earth’s rotation can change as a result of several internal and external processes, each of which is at a different timescale. Here, we present some possible connections between the Earth’s rotation variations and the geomagnetic reversal frequency rates over the past 120 Myr. In addition, we show the possible relationship between the geomagnetic field reversal frequency and the δ18O oscillations. Because the latter reflects the glacial and interglacial periods, we hypothesize that it can be used as a possible indicator to explain the length of day (LOD) variations and consequently the reversal field frequency over the past 510 Myr. Therefore, our analysis suggests that the relationships between the geomagnetic reversal frequency rates and the Earth’s rotation changes during the Phanerozoic. However, more reversal data are required for periods before the KRS to strengthen the perspective of using the geomagnetic reversal data as a marker for the LOD variations through geological times.